In-vitro Bioactivity Assessment of PLA/Hydroxyapatite Synthesized from Cockle Shell Waste in Simulated Body Fluid - Zulkefli, Nursyazwani; Mohammad Ivan Azis,; Shahzulreza Saiful,; Eliza M.Yusup, (International Journal of Integrated Engineering, 2026)
The development of sustainable biomaterials for bone tissue engineering has garnered significant attention, particularly in utilising waste materials as precursors for bioactive ceramics. This study investigates the in vitro bioactivity of polylactic acid (PLA)/hydroxyapatite (HAp) composites, where HAp was synthesized from cockle shell waste through chemical precipitation. Six composite formulations containing 10%, 20%, and 30% HAp by weight, synthesized at two calcination temperatures (850°C and 900°C). Scanning Electron Microscopy (SEM) analysis revealed minimal apatite formation after 7 days across all compositions, while extensive, uniform apatite crystal coverage was observed after 21 days of immersion. The 20% HAp composite demonstrated optimal bioactivity with complete apatite coverage and favourable morphological characteristics, correlating with previously reported superior mechanical properties with Young's modulus of 8.71 GPa. Energy Dispersive X-ray (EDX) analysis confirmed calcium and phosphorus deposition consistent with apatite formation. The 21-day timeline for complete apatite formation aligns well with bone healing phases, suggesting excellent potential for clinical applications. This study validates cockle shell-derived HAp as a bioactive component in PLA composites, offering a sustainable alternative to commercial HAp while demonstrating excellent biocompatibility for bone tissue engineering applications.